DINAMIKA PERAN, PERLAWANAN, DAN KEKUASAAN PEREMPUAN PERSPEKTIF FEMINISME DALAM NOVEL DAULAH SAYYIDAT FI MAMLAKAH NISA KARYA NIQULA HADDAD - Dea Maharani; Mohamad Rohman; Ahmad Habibi Syahid; St Zakiatul Fadila (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2026)
Gender inequality that places women in subordinate positions within patriarchal systems has been widely criticized in feminist studies. In literary works, criticism of such systems is often represented through female characters who not only perform social roles but also engage in resistance and establish power within society. The novel Daulah Sayyidat Fi Mamlakah Nisa by Niqula Haddad portrays a society led by women as a critique of male domination. However, the dynamics of women’s roles, resistance, and power represented in the novel still require more comprehensive scholarly examination. Therefore, this study aims to analyze the dynamics of women's roles, the forms of women's resistance to patriarchal domination, and the construction of women's power from a feminist perspective in the novel. This research employs a qualitative descriptive method with a feminist literary criticism approach. The data consist of words, phrases, sentences, and dialogues that represent women's roles, resistance, and power, collected through reading and note-taking techniques and analyzed using content analysis. The findings reveal that women are depicted as having strategic roles as state leaders, political decision makers, and drivers of education and culture. Furthermore, women resist male domination and establish new structures of power that influence gender relations within society.